ILO declaration on social justice for a fair globalization (ILO GenevaCH, 2008)
Is the third major statement of principles and policies adopted by the International Labour Conference since the ILO's Constitution of 1919. Builds on the Philadelphia Declaration of 1944 and the Declaration on Fundamental Principles and Rights at Work of 1998. Expresses the contemporary vision of the ILO's mandate in the era of globalisation. Institutionalises the Decent Work concept developed by the ILO since 1999, placing it at the core of the Organisation's policieis to reach its constitutional objectives.
Keywords: SOCIAL JUSTICE